Effect of drought stress on different physiological traits in bread wheat (SAARC Journal of Agriculture, 2018)
The present study was designed to evaluate the changes in different physiological traits such as proline content, cell membrane stability, relative water content and chlorophyll content under drought stress in sixteen wheat genotypes. Wheat genotypes (99FJ-03, Marvi-2000, WC- 13, WC-24, WC-19, Faisalabad-85, Kaghan, Bahawalpur, Zarlashta, Punjab-96, Shafaq, Maxi-pak, WC-20, Chenab-70, AUR-0809, Chakwal) were sown during rabiseason of 2013-14 following randomized complete block design with three replications. Drought stress was induced by withholding water for 30 days at heading and anthesis stage. Genotypes were significant for different physiological traits like relative water content, proline content, cell membrane stability and chlorophyll content under drought stress which indicated that some genotypes were more tolerant against drought stress than others. Among tested wheat genotypes, Maxi-Pak was found to be potential variety for relative water content, cell membrane stability, chlorophyll content and yield. Hence, it can be used in future wheat breeding programme for developing drought tolerant genotypes.SAARC J. Agri., 16(1): 1-6 (2018)